2004
DOI: 10.1038/nsmb859
|View full text |Cite|
|
Sign up to set email alerts
|

Structures of human MAP kinase kinase 1 (MEK1) and MEK2 describe novel noncompetitive kinase inhibition

Abstract: MEK1 and MEK2 are closely related, dual-specificity tyrosine/threonine protein kinases found in the Ras/Raf/MEK/ERK mitogen-activated protein kinase (MAPK) signaling pathway. Approximately 30% of all human cancers have a constitutively activated MAPK pathway, and constitutive activation of MEK1 results in cellular transformation. Here we present the X-ray structures of human MEK1 and MEK2, each determined as a ternary complex with MgATP and an inhibitor to a resolution of 2.4 A and 3.2 A, respectively. The str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
468
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 575 publications
(497 citation statements)
references
References 37 publications
21
468
0
4
Order By: Relevance
“…7, A-C, data not shown). Loop 1, in particular, is a stretch of all-negative residues that could potentially interact with residues of MKK7 involved in binding to the three-phosphate group of ATP (27,30). This hypothesis is strongly supported by experimental evidence, because the basic residue-rich region 132-156 (comprising ␤2 and ␤3) was previously identified as a dominant Gadd45␤-binding site of MKK7 (11).…”
Section: Gadd45␤ Regions Mediating Suppression Of Tnf␣-induced Pcd-supporting
confidence: 56%
See 2 more Smart Citations
“…7, A-C, data not shown). Loop 1, in particular, is a stretch of all-negative residues that could potentially interact with residues of MKK7 involved in binding to the three-phosphate group of ATP (27,30). This hypothesis is strongly supported by experimental evidence, because the basic residue-rich region 132-156 (comprising ␤2 and ␤3) was previously identified as a dominant Gadd45␤-binding site of MKK7 (11).…”
Section: Gadd45␤ Regions Mediating Suppression Of Tnf␣-induced Pcd-supporting
confidence: 56%
“…8; also supplementary Fig. S4) (27,30). Indeed, in this model, the ATP-binding site of MKK7 is formed by a number of highly conserved residues (27,30).…”
Section: Gadd45␤ Regions Mediating Suppression Of Tnf␣-induced Pcd-mentioning
confidence: 99%
See 1 more Smart Citation
“…Structural studies with an analog of CI-1040 in complex with MEK1 or MEK2 showed inhibitor binding did not perturb ATP binding, and instead, bound to a unique inhibitor binding pocket adjacent to the ATP-binding site (Ohren et al, 2004). Inhibitor binding locked MEK in a catalytically inactive conformation.…”
Section: Mek Inhibitorsmentioning
confidence: 99%
“…MEK inhibitors are very specific and do not inhibit many different protein kinases including p38 MAPK and JNK (Davies et al, 2000). The crystal structures of MEK1 and MEK2 have been determined as ternary complexes with ATP and PD184352 and have revealed that both MEK1 and MEK2 have unique inhibitor binding sites located on a hydrophobic pocket adjacent to but not overlapping with the ATP binding site (Ohren et al, 2004). Furthermore, effective targeting of MEK1,2 is highly specific as ERK1,2 are the only well-described downstream targets.…”
Section: Therapeutic Targeting Of the Pi3k/akt/pten/mtor And Raf/mek/mentioning
confidence: 99%